PENGARUH PEMBERIAN JUS ALPUKAT, MADU, DAN COKLAT HITAM (JUS AMACO) TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERTA HIPERTENSI DI PANTI SOSIAL KOTA PALEMBANG - Muzakar, Muzakar; Rahman, Imeliana; Listrianah, Listrianah (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2023)
Background : Someone who experiences an increase in blood pressure exceeds the systolic value of 140 mmHg and a diastolic 90 mmHg is called hypertension (RI Ministry of Health, 2014). The results of the Basic Health Research (Riskesdas) in 2013 showed that the prevalence of hypertension in Indonesia was 25.8% and the prevalence of hypertension in South Sumatra was 26.1%. Objective : This study aims to determine the effect of giving avocado juice, honey, and dark chocolate (amaco juice) to the reduction of blood pressure in elderly people with hypertension on the Tresna Werdha Teratai Palembang Social Home. Method : This type of research was quasi-experimental with a treatment and comparison group conducted in January 2019 at the Tresna Werdha Teratai Palembang Social Home. The number of samples in this study were 50 elderly consisting of 25 elderly treatment groups and 25 elderly comparison groups.Result : The results of this study indicate that based on sex most of the women are in the treatment group by 60% (15 people) and in the comparison group by 72% (18 people). Based on age in the treatment group, most of the age group> 70 years were 13 people (52%) and in the comparison group there were 18 people (72%). Conclusion : The results of statistical tests showed that the value (p <0.05) p-value <0.05 so it can be concluded that there was the effect of AMACO juice on the reduction of blood pressure in elderly people with hypertension on the Social Institution of Tresna Werdha Teratai Palembang.